Educação escolar indígena: um estudo sociolinguístico do Nheengatu na escola Puranga Pisasú do Rio Negro, Manaus-AM. - Lima, Ademar dos Santos (2018)
The present study aims to reflect on the Indigenous School Education proposed by the Municipal Education Department of Manaus and the sociolinguistic situation of the nheengatu speakers having as reference an indigenous school of the community Pisasú Sarusawa/ Nova Esperança, of the Baré ethnic group in the Municipality of Manaus - AM. The main objective was to analyze if in the community in study the teaching practices in the indigenous school promote the strengthening of Nheengatu. The methodologies used were qualitative-quantitative approach, field research, descriptive study and the techniques used were semi-structured questionnaire, interview and participant observation. A total of 128 informants were interviewed on skills and abilities in nheengatu speech. The study found that of these, only 25, in the age group above 40 years, speak the ethnic language fluently; 68, in the age group between 12 and 39 years old they understand and can speak some words and expressions; 35, in the age group of 4 to 11 years do not speak and only understand the indigenous language. The study also verified that there was a discontinuity in the transmission of Nheengatu among this group of speakers, who started to speak more Portuguese. Currently the Nheengatu goes through the revitalization process in the Pisasú Sarusawa community of the Baré people. Keywords: Indigenous language; Bilingualism; Revitalization.